Edukasi Pemanfaatan Tanaman Obat Tradisional untuk Kesehatan Lansia di Panti Werda Berbasis Edukasi Interaktif - Shirly Gunawan; Bruce Edbert; Devi Putri Nabila; Elisya Shafa Ananda Maurika; Taufik Rizky Marhaen; Dodo Nugroho; Theresa Vanya Nabela Puspita Prameswari; Stephanie Amadea; Jennifer Oscar (Amalee: Indonesian Journal of Community Research and Engagement, 2026)
Indonesia, with its rapidly growing elderly population (12% today, projected to reach 20% by 2045), faces major challenges in sustaining the quality of life of older adults. Comprehensive strategies are required to keep the elderly active, healthy, and productive, including the role of nursing homes that provide integrated health services. One promising approach is the use of traditional medicinal plants, globally recognized but remain relatively unfamiliar among the elderly. This community service program aims to educate elderly nursing home residents on the use of traditional medicinal plants. This activity adopted an educational approach using interactive games. Sixty-three elderly participants were divided into six groups. The program employed a descriptive qualitative approach supported by simple quantitative pre‑ and post‑test data to achieve a comprehensive understanding of its effectiveness. Initial knowledge was limited (83.33% scored 3–4), but after the educational intervention, four groups (66.67%) achieved excellent scores (9–10), one group (16.67%) attained good scores (7–8), and one group attained average scores (5-6). In the quiz, all questions (100%) were answered correctly. These findings highlight that interactive education can significantly improve elderly knowledge and motivation, offering a sustainable model for promoting the safe and effective use of traditional medicinal plants.